(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the disease patterns of Otorhinolaryngology (ENT) and analyze the associations with demographic and seasonal factors at a preventive and general health facility in 2024. Methods: A retrospective descriptive study was conducted using data from the Hospital Information System (HIS) of 1,545 ENT outpatients throughout 2024.Results: The mean age was 13.7 ± 20.1, with children under 6 years old accounting for 62.5%. Acute conditions predominated at 94.4%. Disease distribution by region was: Nose and Sinus (59.2%), Ear (20.9%), and Throat-Larynx (19.5%). The five most common ICD-10 codes were: Acute nasopharyngitis (43.2%), Acute serous otitis media (10.2%), Acute sinusitis (8.8%), Allergic rhinitis (6.2%), and Acute suppurative otitis media (6.2%). There were statistically significant associations between disease patterns and age groups (p< 0.01) and seasonal quarters (p< 0.01); however, no significant difference was observed by gender (p> 0.05).Conclusion: The ENT disease pattern primarily consists of acute inflammatory conditions in preschool-aged children with significant variations depending on the time of the year, highlighting the need for proactive community-based preventive strategies.